2016
DOI: 10.1136/jnnp-2016-314597.273
|View full text |Cite
|
Sign up to set email alerts
|

L18 Tryptophan-2,3-dioxygenase (TDO) inhibition ameliorates neurodegeneration by modulation of kynurenine pathway metabolites

Abstract: BackgroundThe kynurenine pathway (KP), the major catabolic route of tryptophan (TRP) metabolism, has been closely linked to the pathogenesis of several brain disorders. This pathway produces several neuroactive metabolites, including 3-hydroxykynurenine (3-HK), quinolinic acid (QUIN) and kynurenic acid (KYNA). A shift towards the synthesis of neurotoxic 3-HK and QUIN relative to neuroprotective KYNA has been found in Huntington’s disease (HD) patients and models. In a Drosophila model of HD, genetic inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is an important functional amino acid with a variety of nutritional and physiological functions. 1 It is indicated that many diseases are associated with TRP metabolism disorders, such Huntington's disease, 3 and gastrointestinal diseases 4 to name a few, also, miscarriage. 2 In recent years, a large number of studies have shown that tumor growth is closely related to TRP metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important functional amino acid with a variety of nutritional and physiological functions. 1 It is indicated that many diseases are associated with TRP metabolism disorders, such Huntington's disease, 3 and gastrointestinal diseases 4 to name a few, also, miscarriage. 2 In recent years, a large number of studies have shown that tumor growth is closely related to TRP metabolism.…”
Section: Introductionmentioning
confidence: 99%